Urban Film space in Cartagena: 1936-1957 - Chica Geliz, Ricardo (Universidad Pedagógica y Tecnológica de Colombia, 2014)
By means of the concept of “urban ilm space”, it is possible to study the practices and uses of the reception of ilms, viewed by different social sectors of Cartagena, especially Mexican ilms of the Golden Age (1936-1957). Three aspects were examined for this analysis: the periodization of urban ilm space in Cartagena, the social use of ilm and its daily practices, and the case of the strike of theaters in 1955. These aspects allow us to situate and comprehend the symbolic place that different ilm audiences occupied, as well as their speciic conditions of life in a context of strong social exclusion.